Dunging gutters filled with fresh water in finishing barns had no effect on the prevalence of Salmonella enterica on Brazilian swine farms - Oliveira, CJB; Carvalho, LFOS; Domingues, F. J.; Menezes, CCP; Fernandes, S. A.; Tavechio, A. T. (Elsevier B.V., 2002)
Our aim was to assess the importance of dunging gutters filled with water in finishing barns for the prevalence of pigs shedding Salmonella enterica. Some finishing barns in Brazil are provided with a dunging-gutter system which consists of a continuous water flow at the back of solid-floored adjacent pens. Because there is transfer of faecal material between adjacent pens by water in this system and the faecal-oral route of transmission is so important for enteric pathogens, we tested the hypothesis that the presence of this kind of dunging-gutter system in finishing barns affects the prevalence of slaughter-age pigs shedding salmonella organisms in their faeces. The cross-sectional study was conducted on six farms each having barns with and barns without a dunging-gutter system. Breeding, management, nutritional and seasonal factors were similar in both barns on each farm. The two systems did not differ in prevalence of pigs shedding salmonella organisms. Five S. enterica scrotypes were isolated: S. Agona, S. Javiana, S. Rissen, S. Sandiego and S. Senftenberg. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: dunging gutters; finishing barns; pigs; Salmonella epidemiology; swine; water